Effect of State Bonds on the Private Sector: Evidence from a Growing Economy - C. O. Omodero (Финансы: теория и практика, 2024)
The frequent issuance of state bonds or securities by the government in the stock market crowds out the private sector in developing economies. The main concern is whether the economy can continue to function normally in the face of this occurrence if it is not checked. We use an Autoregressive Distributed Lag (ARDL) co-integration approach to confirm this scenario using data from the World Development Indicator and the Central Bank of Nigeria, spanning 1989 to 2021. The analysis’ findings indicate that lowering borrowing costs will not put a strain on the private sector. However, thecurrent government borrowing domestically has no significant positive influence, confirming that if the government does not reduce the amount of securities in the stock market, investors will continue to invest in government bonds while ignoring corporate bonds. This finding implies that the economy will not be in parity because private sector investment will be stifled. In accordance with the study, the government should promote private sector operations by lowering interest rates and regulating borrowing limits to ensure that they do not exceed the threshold that is beneficial to both the economy and private sector operations.